25 A Pilot Implementation of Providing Enhanced Support to Care Homes within A Primary Care Network. (6th February 2020) - Didehvar, R; Ehtheshamirad, G; Batty, G; Sage, S; Mullins, S; Thomas, C
Abstract: Introduction: People living with severe frailty in care homes are vulnerable to frequent non-elective hospital attendances. However provision of enhanced healthcare support to care home residents can reduce this risk and increase quality of life for residents. 1 The framework for enhanced health in care homes (EHCH) summarises best practice in this area and provides guidance for implementing services. 2 Methods: This study was a pilot implementation of the EHCH framework based on a Primary Care and Specialist Frailty Multidisciplinary Team (MDT) and delivered on a Primary Care Network (PCN) footprint. The MDT targeted five care homes in a PCN area with historically high levels of non-elective attendances. The model of care was based on the principle of anticipatory care planning, training and support for care home staff to understand and implement plans. Results: Over the pilot period of 9 months, non-elective attendances from the 5 homes reduced by 27% compared to the previous year, which was a significant reduction (p<0.042). There was variation between the homes in the reduction in non-elective attendances with the greatest impact seen in the homes that had the highest level of attendance at training and engagement in the care planning process. Feedback received from the care home staff indicated that they felt more confident to refer to the care plans and had alternative options to calling 999. A quality audit of the care plans completed as part of the pilot revealed a number of additional training needs for clinicians completing the plans to ensure consistency of recoding. This training was delivered following the pilot period. Conclusions: The pilot demonstrated that the EHCH framework could be successfully implemented on a PCN footprint. Analysis shows this implementation coincided with a reduction in non-elective attendances from the targeted homes. Further analysis is required to compare the impact in different homes and to understand contributing factors. The pilot implementation provides helpful information to inform PCN development. References: 1. Lloyd T, Wolters A and Steveton A (2014) The impact of providing enhanced support for care home residents in Rushcliffe: Health Foundation consideration of findings from the Improvement Analytics Unit. The Health Foundation. 2. NHS England (2016) The framework for enhanced health in care homes.